2016
DOI: 10.1016/j.lisr.2016.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Watching young children “play” with information technology: Everyday life information seeking in the home

Abstract: Highlights Young children engage with technology in artistic play, socio-dramatic play and literacy/numeracy.  Everyday life information seeking (ELIS) way of life and mastery of life are modeled in children's activities.  Video data provide a glimpse into technology use by young children in their homes. AbstractResearch on how young children use information to orient themselves in daily life and to solve problems (known as everyday life information seeking or ELIS) has not been conducted, indepth, in infor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 66 publications
2
30
0
Order By: Relevance
“…Research on information access, seeking, and representation in leisure settings, migration, healthcare, and the home has expanded information science beyond contexts such as schools and libraries, which continue to be focal points in the field (Allard 2015;Cox and Blake 2011;Dali 2013;Given et al 2016;Gorichanaz 2015;Hartel 2010;Lloyd 2014a;Loudon, Buchanan, and Ruthven 2016;McKenzie 2010;Quirke 2015;Tinto and Ruthven 2016;Huvila 2013;Lloyd 2009;Molopyane and Fourie 2015;Pilerot 2016;Takhteyev 2012). Although religious practice is another important part of everyday life (refer to, e.g., Statistics Canada 2013), with the exception of a small number of studies on information seeking and use among Christian clergy (e.g., Michels 2014;Roland 2012;Roland and Wicks 2009), research about the role of information in religious practice remains marginal.…”
Section: Introductionmentioning
confidence: 99%
“…Research on information access, seeking, and representation in leisure settings, migration, healthcare, and the home has expanded information science beyond contexts such as schools and libraries, which continue to be focal points in the field (Allard 2015;Cox and Blake 2011;Dali 2013;Given et al 2016;Gorichanaz 2015;Hartel 2010;Lloyd 2014a;Loudon, Buchanan, and Ruthven 2016;McKenzie 2010;Quirke 2015;Tinto and Ruthven 2016;Huvila 2013;Lloyd 2009;Molopyane and Fourie 2015;Pilerot 2016;Takhteyev 2012). Although religious practice is another important part of everyday life (refer to, e.g., Statistics Canada 2013), with the exception of a small number of studies on information seeking and use among Christian clergy (e.g., Michels 2014;Roland 2012;Roland and Wicks 2009), research about the role of information in religious practice remains marginal.…”
Section: Introductionmentioning
confidence: 99%
“…This paper presents the quantitative results of the analysis. An inductive, thematic analysis was also completed with the dataset, to examine the children's activities in the context of the theory of everyday life information seeking; those results are published elsewhere (Given et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…In her study, Palaiologou (2016) reported that digital activities were integrated into children's interactions with parents and personal explorations. In an observational study, Given et al (2016) found evidence that young children can combine digital technologies with their social and dramatic play and their offline literacy and numeracy learning in the home. Overall, few studies have focused their attention on children's agency or creative use of digital media in homes.…”
Section: Research Insights Into Children's Digital Literacy Practicesmentioning
confidence: 99%